Covid-19 and social care: Union strategies to reshape a dysfunctional sector. (1st June 2021) - Nelson, Kevan
Abstract : In volume 120 of Theory and Struggle (pp. 124-33), I described Unison North West's Care Workers for Change campaign and how our multidimensional approach to organising in the care sector was informed by the work of John Kelly (Rethinking Industrial Relations: Mobilization, Collectivism and Long Waves, 1998) and Jane McAlevey (No Short Cuts: Organizing for Power in the New Gilded Age, 2016). The Covid-19 pandemic has subsequently brought unprecedented catastrophe and human suffering to vulnerable people and workers in our dysfunctional social care system. This contribution first describes the impact of Covid-19 on social care and union responses to it. The focus then turns to competing ideas about how the social care system might be reshaped and the role of unions in pursuing meaningful structural and institutional change that could win lasting improvements for care workers.